Big data analysis techniques for image warehouse architecture - Tereshchenko, G. (ХНУРЕ, 2024)
With the rapid growth of image data in recent years, efficient management and retrieval of image data have become increasingly important. In this paper, we propose an image warehouse architecture in the era of big data that combines data preprocessing, compression and deduplication, distributed processing and parallel computing, machine learning and deep learning, and security and privacy techniques to improve the efficiency and scalability of image warehouse. We conducted experiments o a large-scale image dataset, and the results show that our approach significantly outperforms existing methods in terms of retrieval accuracy and efficiency. The proposed architecture provides a promising solution for managing and retrieving large-scale image data in the era of big data. Зі стрімким зростанням у останні роки обсягів зображень ефективне управління та пошук зображень набувають все більшої важливості. У цій статті пропонується архітектура сховища зображень в епоху великих даних, яка поєднує попередню обробку даних, компресію та видалення дублікатів, розподілену обробку та паралельні обчислення, методи машинного та глибинного навчання, а також техніки забезпечення безпеки та конфіденційності для підвищеnння ефективності та масштабованості сховища зображень. Проведені експерименти на великому наборі зображень, і продемонстровані результати, що даний підхід перевершує існуючі методи за точністю та ефективністю пошуку. Запропонована архітектура забезпечує перспективне рішення для управління та пошуку зображень в епоху великих даних.
Keywords: data mining; big data; image; knowledge management; warehouse; image warehouse; business intelligence; machine learning; deep learning; neural networks; image recognition; image annotation; data visualization; text analytics; text-graphic documents; metadata; дата майнінг; великі дані; сховище зображень; бізнес-аналітика; глибинне навчання; нейронні мережі; анотація зображень; візуалізація даних; аналітика тексту; текстово-графічні документи; метадані; метадані; метадані